2012
DOI: 10.4319/lom.2012.10.653
|View full text |Cite
|
Sign up to set email alerts
|

GEOTRACES IC1 (BATS) contamination‐prone trace element isotopes Cd, Fe, Pb, Zn, Cu, and Mo intercalibration

Abstract: The stable isotope composition of radiogenic and natural elements provides a powerful tool for unraveling element sources and biogeochemical processes in the marine environment. Depending on the element, trace element isotope ratios can (1) narrow possible sources of the element in a sample and/or (given a temporal history boundary condition) constrain the time the when the element departed the ocean surface (e.g., Pb, Nd), (2) provide information on redox processes that the element is directly or indirectly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 37 publications
8
93
0
Order By: Relevance
“…The analytical protocol has been previously published (46), validated by the GEOTRACES intercalibration exercise (47) and an intercomparison study (48).…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…The analytical protocol has been previously published (46), validated by the GEOTRACES intercalibration exercise (47) and an intercomparison study (48).…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…On each analytical date, we calibrated the instrument by running NBS981 and normalized measured sample isotope 30 ratios to our measured raw NBS981 isotope ratios to those established by Baker et al (2004) We have intercalibrated Pb isotope analyses with two labs as reported in Boyle et al (2012). The outcome of that intercalibration suggests that the accuracy of our measurements approaches the internal analytical reproducibility we note above.…”
Section: Stable Pb Isotopesmentioning
confidence: 99%
“…GEOVIDE samples were analysed during 11 mass spectrometry sessions by the method of Reuer et al (2003) as modified by Boyle et al (2012). In brief, ~500mL of seawater was pre-concentrated using a low-blank double magnesium hydroxide co-precipitation, induced by minimal addition of high-purity ammonia solution and mixing 15 (typically 8µL ammonia per 1mL seawater sample).…”
Section: Stable Pb Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel, iron and other bioactive trace metals are key to understanding global biogeochemical cycles. Efforts to map the global distributions of dissolved and particulate trace metals is progressing especially with the recent international GEOTRACES field expedition results (Bishop et al 2012;Boyle et al 2012;Noble et al 2012;Rousseau et al 2013;Butler et al 2013;Twining and Baines 2013;Kondo and Moffett 2013). Expanding surveys of trace metals allow more detailed investigation on the relationship between primary, secondary, and colimiting nutrients (Arrigo 2005;Moore et al 2013).…”
Section: Introductionmentioning
confidence: 99%